The PI3K/AKT/mTOR canonical pathway and its alterations in cancer - Aldecoa, F. (2021)
The PI3K/AKT/mTOR pathway is involved in multiple cellular processes which are essential for the cells. Some genetic mutations of the components of this pathway have been associated with various human diseases, the most important of which are breast, thyroid and endometrium carcinomas; glioblastoma multiforme; prostate cancer and lymphomas. ThePI3K/AKT/mTOR canonical pathway has been extensively studied in recent years. However, as the complexity of its main components and their correlation with the components of other pathways are increasing, it is important to update fromtime to time the available information to understand this mechanism. Furthermore, many trials have been conducted with selective medicines aimed to look for a more intelligent treatment for diseases associated with alterations in this pathway. Therefore, we review this transduction pathway to take a close look at its functioning and alterations, and to list some promising molecules for future treatments.